2019
DOI: 10.1155/2019/2305318
|View full text |Cite
|
Sign up to set email alerts
|

The Modulatory Effect of Cerebrovascular Burden in Response to Cognitive Stimulation in Healthy Ageing and Mild Cognitive Impairment

Abstract: Background. Cerebrovascular burden is a common pathology in mild cognitive impairment (MCI) and Alzheimer’s disease (AD), with an additive impact on cognitive functioning. Despite being proposed as a potential moderator of cholinesterase inhibiting drug therapy, there is a paucity of evidence investigating the impact of cerebrovascular pathology on responsiveness to cognitive interventions. Method. The current study uses neuropsychological, neurostructural, and functional connectivity indices to characterise r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…Accordingly, two studies found that compared to standard care, 8-week CR and 7-week CS programs could improve fMRI even in individuals with mild dementia ( 14 , 15 ). Interestingly, Bentham et al observed that individuals with high vascular burden had a lower functional connectivity response to CS than those with low burden, suggesting that vascular pathology could limit the potential for a neuroplastic response to cognitive interventions ( 16 ).…”
Section: Tackling Cognitive Decline Symptoms Through Improved Cogniti...mentioning
confidence: 99%
“…Accordingly, two studies found that compared to standard care, 8-week CR and 7-week CS programs could improve fMRI even in individuals with mild dementia ( 14 , 15 ). Interestingly, Bentham et al observed that individuals with high vascular burden had a lower functional connectivity response to CS than those with low burden, suggesting that vascular pathology could limit the potential for a neuroplastic response to cognitive interventions ( 16 ).…”
Section: Tackling Cognitive Decline Symptoms Through Improved Cogniti...mentioning
confidence: 99%
“…While numerous preclinical and clinical trials demonstrated some beneficial effects of different types of physical exercise on AD biomarkers, the data on the effects of cognitive interventions are scarce. Among participants with MCI or healthy elderly people, who participated in computerized cognitive stimulation during 20 sessions, those with the higher vascular burden (regarding the volume of white matter hyperintensities) had a decreased neuroplastic response (assessed as upregulation in functional connectivity within the brain default mode network) to this intervention [49]. In a rat model, physical or cognitive exercise reversed the decrease in hippocampal lipid peroxidation, and restored Aβ infusion-impaired hippocampal AChE activity, and hippocampal tissue disorganization, but did not improve lowered total antioxidant capacity [26].…”
Section: Cognitive Interventionsmentioning
confidence: 99%
“…The Lesion Growth Algorithm (LGA) function was applied at a threshold of κ = 0.3 and the resulting individual WMH volume, expressed in ml, was divided by its respective TIV to obtain a fractional index of white matter lesion volume. A κ = 0.3 has been indicated as the best performing threshold by an earlier methodological study (Schmidt et al, 2012) and has been used in previous research as the optimal value to separate WMH from normal tissue (De Marco et al, 2017b;Bentham et al, 2019;Manca et al, 2021).…”
Section: Mri Acquisition and Modellingmentioning
confidence: 99%